2019
DOI: 10.1186/s13148-019-0744-8
|View full text |Cite
|
Sign up to set email alerts
|

Variation of PEAR1 DNA methylation influences platelet and leukocyte function

Abstract: BackgroundPlatelet-endothelial aggregation receptor 1 (PEAR-1) is a transmembrane receptor involved in platelet activation and megakaryopoiesis whose expression is driven by DNA methylation. PEAR1 variants were associated with differential platelet response to activation and cardiovascular outcomes. We aimed at investigating the link between PEAR1 methylation and platelet and leukocyte function markers in a family-based population.ResultsWe measured PEAR1 methylation in 605 Moli-family participants with availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 70 publications
0
22
0
1
Order By: Relevance
“…It sustains αIIbβ3 activation in aggregating platelets and attenuates megakaryopoiesis by controlling the degree of Akt phosphorylation 37 , 38 . Moreover, methylation-controlled PEAR1 expression can activate platelets and have an impact on inflammation 39 41 . Both in vitro and in vivo studies in endothelial cells showed an inverse correlation between PEAR1 expression and vascular assembly, which implies that PEAR1 modifies neo-angiogenesis 42 .…”
Section: Discussionmentioning
confidence: 99%
“…It sustains αIIbβ3 activation in aggregating platelets and attenuates megakaryopoiesis by controlling the degree of Akt phosphorylation 37 , 38 . Moreover, methylation-controlled PEAR1 expression can activate platelets and have an impact on inflammation 39 41 . Both in vitro and in vivo studies in endothelial cells showed an inverse correlation between PEAR1 expression and vascular assembly, which implies that PEAR1 modifies neo-angiogenesis 42 .…”
Section: Discussionmentioning
confidence: 99%
“…21 The modifying effect of the rs12041331-A genotype on association with cardiovascular and bleeding events and aspirin treatment was analyzed using an interaction term in a multivariable Cox regression model. these processes has been platelet aggregation; however, other proposed functions of this receptor include maintenance of endothelial cell function, 13,25 megakaryopoiesis and thrombopoiesis, 7 neoangiogenesis, 26 leukocyte function, 17 and neuronal phagocytosis. 27,28 These and other publications have prompted numerous genetic studies attempting to correlate PEAR1 polymorphisms with related phenotypes and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Since its identification in 2005, multiple investigations have been published highlighting the role of PEAR1 in several important biological processes 5 . The most extensively studied of these processes has been platelet aggregation; however, other proposed functions of this receptor include maintenance of endothelial cell function, 13,25 megakaryopoiesis and thrombopoiesis, 7 neoangiogenesis, 26 leukocyte function, 17 and neuronal phagocytosis 27,28 . These and other publications have prompted numerous genetic studies attempting to correlate PEAR1 polymorphisms with related phenotypes and diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that genetic variants in the PEAR1 gene were not only associated with platelet aggregation ( 8 , 9 ) but also the response to antiplatelet agents including aspirin ( 10 ) and clopidogrel ( 11 ). Rs12041331 is an intronic variant that is supposed to modify PEAR1 expression in the protein level via a different allele-specific DNA methylation and has been found to be correlated with platelet aggregation ( 12 , 13 ). Although there has been evidence that PEAR1 rs12041331 has an effect on agonist-stimulated platelet aggregation in aspirin-treated patients ( 14 ), it is still controversial whether this genetic polymorphism in PEAR1 is associated with clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%